Evaluation of Fluid Flow Velocity Variations on the Plate Heat Exchanger Performance - Andika Syahputra; Asnawi Asnawi; Ahmad Nayan; Alchalil Alchalil; Nurul Islami (TRANSMISI, 2023)
Heat exchanger expected to high effectiveness of heat transfer. Type of plate heat exchanger was more efficient compare to another heat exchangers in industrial applications with pressure less than 30 bar. The increased velocity of cold fluid flow has an impact to increase the performance of heat exchanger by  heat transfer rate (Q), heat transfer coefficient (U), and the effectiveness of heat exchanger (ε). The increased velocity of cold fluid flow also incresing the heat transfer rate. The study carried out by variation of the cold fluid velocity at 0.03 m/s, 0.037 m/s, 0.045 m/s, 0.051 m/s and 0.059 m/s. Inlet hot fluid temperature (Th,i) at 45°C and cold fluid temperature (Tc,i) at 27°C constant. The results shows Q value from the original 1570.71 Watt to 1916.16 Watt on the hot side and 1751.89 Watt to 2187.01 Watt on the cold side. The U value from the original 1180.46 W/m2.°C becomes 1408,75 W/m2. °C. The ε value increased from 60.33% to 75.69%. The increasing of  cold fluid velocity directly proportional to the the heat transfer rate (Q) and performance of the plate heat exchanger. This Phenomenon due to the faster circulation of the cold fluid, which causes the cold fluid to quickly return to its initial temperature (Th,i), an than increasing the plate heat exchanger's performance.